Promotion with and without Learning : Effects on Student Enrollment and Dropout Behavior - King, Elizabeth M.; Orazem, Peter F.; Paterno, Elizabeth M. (World Bank, Washington, DC, 2012)
Many educators and policymakers have argued for lenient grade promotion policy - even automatic promotion - in developing country settings where grade retention rates are high. The argument assumes that grade retention discourages persistence or continuation in school and that the promotion of children with lower achievement does not hamper their ability or their peers' ability to perform at the next level. Alternatively, promoting students into grades for which they are not prepared may lead to early dropout behavior. This study shows that in a sample of schools from the Northwest Frontier Province of Pakistan, students are promoted primarily on the basis of merit. An econometric decomposition of promotion decisions into a component that is based on merit indicators (attendance and achievement in mathematics and language) and another that is uncorrelated with those indicators allows a test of whether parental decisions to keep their child in school is influenced by merit-based or non-merit-based promotions. Results suggest that the enrollment decision is significantly influenced by whether learning has taken place, and that grade promotion that is uncorrelated with merit has a negligible impact on school continuation.